2019
DOI: 10.1101/727206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal variation in small mammal abundance and diversity under protection, pastoralism and agriculture in the Serengeti Ecosystem, Tanzania

Abstract: 15Land use is an important factor influencing animal abundance, species richness and 16 diversity in both protected and human-dominated landscapes. Increase in human population 17 and activities intensify changes in habitat structure and hence abundance, species richness and 18 diversity. We investigated the influences of land use and seasonality on small mammal 19 abundance, species richness and diversity in 10 habitat types distributed over protected, 20 agricultural and pastoral landscapes in the Serengeti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…As expected, diversity of the small mammals was lowest in the cropland compared to the non-crop habitats (including homestead). The results are in agreement with Demeke et al (2007), Mayamba et al (2019) and Shilereyo et al (2019) who also reported higher small mammal diversities in non-cultivated areas than in agricultural fields in Ethiopia (Arba Minch area), Uganda and Tanzania, respectively. The low small mammal species diversity in cropland can be ascribed to higher disturbance due to human activities including; land preparation (ploughing), weeding, thinning of young plants (particularly maize) and harvesting.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, diversity of the small mammals was lowest in the cropland compared to the non-crop habitats (including homestead). The results are in agreement with Demeke et al (2007), Mayamba et al (2019) and Shilereyo et al (2019) who also reported higher small mammal diversities in non-cultivated areas than in agricultural fields in Ethiopia (Arba Minch area), Uganda and Tanzania, respectively. The low small mammal species diversity in cropland can be ascribed to higher disturbance due to human activities including; land preparation (ploughing), weeding, thinning of young plants (particularly maize) and harvesting.…”
Section: Discussionsupporting
confidence: 92%
“…Of the captured small mammals, 237 were captured in the park, 277 in the pastoral land and 98 in the agricultural land. The total of 28,200 trap nights of effort consisted of 11,280 trap nights in the park, 11,280 in the pastoral land and 5640 in the agricultural land (for more details see Shilereyo et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This involved assessing how ectoparasite load varied between land use, habitat type, season and host species and with the age, sex and breeding status of the host Human disturbance apparently increases ectoparasite load per individual most likely by reducing habitat heterogeneity and altering small mammal species diversity. Indeed, the pastoral and agricultural lands supported fewer small mammal species but numerically more abundant than the protected park (Shilereyo et al 2020). The reduced species diversity in the disturbed pastoral and agricultural lands may increase ectoparasite load (Van Deventer and Nel 2006;Civitello et al 2015;Peng et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ship or Black Rat (Rattus rattus), Norway or Brown Rat (Rattus norvegicus), House Mouse (Mus musculus), Greater Egyptian Gerbil (Gerbillus pyramidis) and Lesser Egyptian Jerboa (Jaculus jaculus) are common rodent species trapped in various ecosystems within the Gaza Strip for both control and scientific purposes as pointed out by Abd Rabou et al (2007a) and Abd Rabou (2019a and c). Such traps are commonly used in studies dealing with small and medium-sized mammals (Shilereyo et al, 2020). Pit traps were rarely used in the Gaza Strip, especially in its western belt which is characterized by its sand dunes topography.…”
Section: Discussionmentioning
confidence: 99%